The effects of biodiesels on semivolatile and nonvolatile particulate matter emissions from a light-duty diesel engine - Yuan Cheng; Li, Shao-Meng; Liggio, John; Hayden, Katherine; Han, Yuemei; Stroud, Craig; Chan, Tak; Poitras, Marie-Josee (ENVIRONMENTAL POLLUTION, 2017)
Semivolatile organic compounds (SVOCs) represent a dominant category of secondary organic aerosol precursors that are increasingly included in air quality models. In the present study, an experimental system was developed and applied to a light-duty diesel engine to determine the emission factors of particulate SVOCs (pSVOCs) and nonvolatile particulate matter (PM) components at dilution ratios representative of ambient conditions. The engine was tested under three steady-state operation modes, using ultra-low-sulfur diesel (ULSD), three types of pure biodiesels and their blends with ULSD. For ULSD, the contribution of pSVOCs to total particulate organic matter (POM) mass in the engine exhaust ranged between 21 and 85%. Evaporation of pSVOCs from the diesel particles during dilution led to decreases in the hydrogen to carbon ratio of POM and the PM number emission factor of the particles. Substituting biodiesels for ULSD could increase pSVOCs emissions but brought on large reductions in black carbon (BC) emissions. Among the biodiesels tested, tallow/used cooking oil (UCO) biodiesel showed advantages over soybean and canola biodiesels in terms of both pSVOCs and nonvolatile PM emissions. It is noteworthy that PM properties, such as particle size and BC mass fraction, differed substantially between emissions from conventional diesel and biodiesels. (C) 2017 Elsevier Ltd. All rights reserved.